Risk factors predicting intracerebral hemorrhage and prognosis of old age patients with mild traumatic brain injury in Hatyai hospital - Maneeon, Pavarada; Promwang, Nattaya (Journal of Medicine and Health Sciences, 2022)
The incidence of mild traumatic brain injury among elderly patients tended to be higher while delaying the diagnosis of intracerebral hemorrhage may create unfavorable clinical outcomes. Therefore, knowing the risk factors or predictive measurement of intracerebral hemorrhage and injury before the emergency department could benefit physicians in terms of decision-making regarding this population. The aim of this study was to identify the risk factors associated with intracerebral hemorrhages, and prognosis among elderly patients with mild traumatic brain injuries who were admitted to Hatyai hospital. A Retrospective study was conducted. The medical records of the elderly patients, aged ≥60 and with mild traumatic brain injury (Glasgow Coma Scale: GCS of 13-15) from January 2016 to December 2020 were reviewed. The study included 501 patients with mean age of 71. Most of the patients were male (n= 254, 50.7%). The most common causes of their injuries were vehicle accidents, (n= 208, 41.5%) and falls (n= 273, 54.5%). Of those, 112 patients (22.4 %) had abnormal results for CT brain. The multivariate analysis showed that seven predictive clinical factors had statistically significant effects on positive CT brain, which included the following: 1) GCS <15; 2) headache; 3) post-traumatic vomiting more than two times; 4) transient loss of consciousness; 5) GCS drop ≥2; 6) clinical signs of skull fracture; and 7) clinical signs of fractures to the base of the skull. At least one clinical predicting factor was statistically significant to identify patients with abnormal intracranial findings in terms of sensitivity = 85.71%, specificity = 50.12% and AUROC = 0.68. Moreover, the normal results for CT scan had significant higher proportion of good prognosis than abnormal results.(p=0.009) Therefore, an elderly patient with mild traumatic brain injury should be carefully evaluated for clinical risk factors. If those risk factors are evident, then a CT brain should be considered.